2014
DOI: 10.1063/1.4891334
|View full text |Cite
|
Sign up to set email alerts
|

InGaN/GaN multiple-quantum-well light-emitting diodes with a grading InN composition suppressing the Auger recombination

Abstract: In conventional InGaN/GaN light-emitting diodes (LEDs), thin InGaN quantum wells are usually adopted to mitigate the quantum confined Stark effect (QCSE), caused due to strong polarization induced electric field, through spatially confining electrons and holes in small recombination volumes. However, this inevitably increases the carrier density in quantum wells, which in turn aggravates the Auger recombination, since the Auger recombination scales with the third power of the carrier density. As a result, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…5, the carrier lifetime is 6.05, 4.66, 4.56 and 3.22 ns for LEDs with 3, 5, 8 and 11 QWs, respectively. The difference among these decay times under the low excitation power is mainly attributed to the different nonradiative recombination rates, which is ascribed to the SRH recombination rate since Auger recombination rate is minor under the low excitation level [21]. Therefore, the reduced carrier lifetime of LED devices with increasing QW number can be a solid support to the claim that in the practical growth a more serious defect-related SRH recombination would be induced in LED devices with more QWs.…”
Section: Resultssupporting
confidence: 50%
“…5, the carrier lifetime is 6.05, 4.66, 4.56 and 3.22 ns for LEDs with 3, 5, 8 and 11 QWs, respectively. The difference among these decay times under the low excitation power is mainly attributed to the different nonradiative recombination rates, which is ascribed to the SRH recombination rate since Auger recombination rate is minor under the low excitation level [21]. Therefore, the reduced carrier lifetime of LED devices with increasing QW number can be a solid support to the claim that in the practical growth a more serious defect-related SRH recombination would be induced in LED devices with more QWs.…”
Section: Resultssupporting
confidence: 50%
“…pol P(x) = ρ ∇ . In our setting, the equivalent negative polarization charge density is induced as Simon et al [26] and Zhang et al [27][28][29][30] suggested. And the polarization charge at the semipolar plane is changed as well due the induced of shear strain and projection angle [31,32].…”
Section: Resultsmentioning
confidence: 92%
“…We have also proposed a gradient InN composition in the quantum wells to suppress the Auger recombination for blue InGaN/GaN LEDs . Two blue InGaN/GaN LEDs are grown by the MOCVD technology and the peak emission wavelength for the two grown LEDs is ∼450 nm.…”
Section: Approaches For Improving the Internal Quantum Efficiencymentioning
confidence: 99%